The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/s1047951121001657
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of home mechanical ventilation with tracheostomy after congenital heart surgery

Abstract: Objective: After congenital heart surgery, some patients may need long-term mechanical ventilation because of chronic respiratory failure. In this study, we analysed outcomes of the patients who need tracheostomy and home mechanical ventilation. Methods: Amongst 1343 patients who underwent congenital heart surgery between January, 2014 and June, 2018, 45 needed tracheostomy and HMV. The median age of these patients was 6.4 months (12 days–6.5 years). Nineteen patients underwent palliatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…The high mortality to current follow-up and in-hospital mortality in our study are striking, though overall consistent with existing literature for pediatric patients with cardiac disease requiring tracheostomy (3–5, 15–23). In-hospital mortality for our cohort is 10-fold higher than in-hospital mortality for all CICU patients during the study period and substantially higher than reported mortality in general pediatric patients with tracheostomy (2, 6, 13, 33–35).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The high mortality to current follow-up and in-hospital mortality in our study are striking, though overall consistent with existing literature for pediatric patients with cardiac disease requiring tracheostomy (3–5, 15–23). In-hospital mortality for our cohort is 10-fold higher than in-hospital mortality for all CICU patients during the study period and substantially higher than reported mortality in general pediatric patients with tracheostomy (2, 6, 13, 33–35).…”
Section: Discussionsupporting
confidence: 90%
“…The key finding of our study was an association between a longer duration of pre-tracheostomy PPV and the hazard of mortality in children with cardiac disease when controlling for other factors. Seven prior studies have described tracheostomy timing relative to total duration of ventilation in pediatric patients including those with congenital heart disease (CHD) (4, 9, 16, 17, 19, 20, 22), but only two specifically compared outcomes based on timing of tracheostomy in children with heart disease (4, 22). A single-institution study of 17 cardiac patients (22) and a multicenter cohort of 126 patients with hypoplastic left heart syndrome (HLHS) (4) both failed to identify an association between duration of ventilation pre-tracheostomy and survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations